The Relationship Between Blood Lactate, Serum Muscle Enzymes, Jumping Performance and Muscle Soreness in Show‐Jumping Horses. (June 2014) - Roberts, C; Harris, P; Murray, R; Cnockaert, R; Roberts, C
Abstract : Introduction: There is relatively little information concerning physiological factors affecting show‐jumping performance. This study examined the relationship between show‐jumping exercise, muscle soreness, serum muscle enzyme activity and blood lactate concentration. Methods: Ten mixed breed horses (9.1 ± 1.9 yrs) were assessed at a British Equestrian Federation (BEF) World Class Performance three‐day training session. Riders received coaching during warm‐up and after jumping a 15 fence course (1.35–1.45 m) once on day one and twice on day two; on day three the second round was an 8 fence jump‐off. Veterinary and physiotherapy assessments of muscle soreness were performed daily before and after exercise. An international coach graded jumping technique. Blood was obtained before and on two occasions after jumping (1 minute, two hours) for measurement of serum CK and AST, and blood lactate concentration. Data were analysed using regression procedures or Spearman correlation, and Wilcoxon signed‐rank test (P<0.05). Results: Blood lactate significantly increased one minute after jumping on all three days (P = 0.003 for all). When two rounds were jumped, lactate was significantly lower after the second round compared to the first (P = 0.006, P = 0.014). There was a positive correlation between blood lactate one minute after jumping and number of faults scored daily and overall (R2 = 0.61; P<0.01), decreased jumping technique grade (R2 = 0.69; P<0.01) and increased gluteal muscle soreness on day two (r = 0.75; P = 0.012). Plasma CK activity one minute, and 2 hours after jumping was significantly higher than before jumping on all days (P<0.01). Conclusions: Horses with higher blood lactate concentrations after jumping demonstrated decreased jumping performance and were more likely to display muscle soreness. Ethical Animal Research: Explicit owner informed consent for participation in this study is not stated.Sources of funding:  The World Class Development Programme is funded by the Department for Culture, Media and Sport, through Exchequer and National Lottery funds, via UK Sport.Competing interests:  none.